A büntetőjogi mediáció gyakorlati aspektusai - Héthy, Eszter (Debreceni Jogi Műhely, 2012)
Mediation is a conflict-management method designed to achieve restorative justice (offenders should assume responsibility and pay the penalty for their deeds, with the greatest emphasis on reparation of the victim, and the affronted community should be conciliated). This method may be applied to solving a variety of disputes or conflicts (e.g. disputes involving neighbours, families, couples, and companies). The mediation technique has already been used in the fields of civil law, family law and employment law. From 2007 onwards, it can also be applied in criminal procedures. According to Article 221/A of the Code on Criminal Procedure (Act XIX of 1998) the mediation process may be used in criminal procedures dealing with certain offences against the person, property or traffic offences if the crime is punishable with no more than five years imprisonment, and the offender has made a confession during the criminal investigation.